2016
DOI: 10.1007/s10815-016-0782-5
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular interleukin-8, interleukin-12, and adrenomedullin are the promising prognostic markers of oocyte and embryo quality in women with endometriosis

Abstract: Purpose The study aimed to investigate key intrafollicular prognostic factors among various cytokines and angiogenic molecules for prediction of mature oocytes and good-quality embryos in women with endometriosis undergoing in vitro fertilization (IVF). Methods Paired follicular fluid and serum samples were collected from 200 women with advanced stage endometriosis and 140 normal ovulating women during oocyte retrieval. The concentrations of cytokines (pro-inflammatory: IL-1β, TNF-α, IL-2, IL-8, IL-12, IFN-γ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
6
64
0
7
Order By: Relevance
“…More recently, two prospective case-control studies found similar results and confirmed significantly lower number of mature oocytes and lower fertilization rates in patients with endometriosis compared to patients with other causes of infertility [24, 74]. In both studies, unfortunately, no information regarding previous surgical treatments received is provided.…”
Section: Endometriosis and Clinical Markers Of Oocyte Qualitymentioning
confidence: 69%
“…More recently, two prospective case-control studies found similar results and confirmed significantly lower number of mature oocytes and lower fertilization rates in patients with endometriosis compared to patients with other causes of infertility [24, 74]. In both studies, unfortunately, no information regarding previous surgical treatments received is provided.…”
Section: Endometriosis and Clinical Markers Of Oocyte Qualitymentioning
confidence: 69%
“…Therefore, no conclusions can be made yet about possible correlations between T and B cells in FF, endometriosis and the effect on folliculogenesis, oocyte maturation and infertility. Singh et al (2016) reported an increase in the levels of pro-inflammatory (IL1B, TNFa, IL2, IL8, IL12) and anti-inflammatory (IL4, IL6 and IL10) cytokines in FF of patients with endometriosis (grade III/IV) undergoing IVF as compared with patients with tubal factor infertility (Box 2). The percentage of mature oocyte and goodquality embryos was significantly lower in endometriosis as compared with controls.…”
Section: T and B Cells In Ff Of Patients With Endometriosismentioning
confidence: 99%
“…У фолликулов имеется метаболически активное микроокружение, в состав которого входят стероидные гормоны, факторы роста, цитокины, свободные радикалы и антиоксиданты наряду с другими элементами, продуцирующимися гранулезными клетками, эндотелиальными клетками и лейкоцитами. В большей степени снижение качества ооцитов коррелирует с повышением содержания IL-8, IL-12, ADM, при этом экспрессия остальных провоспалительных цитокинов также существенно повышена [38]. Один из маркеров окислительного стресса, обнаруженных в перифолликулярной жидкости -миелопероксидаза, может служить потенциальным таргетом при попытках улучшения качества ооцита в программах ВРТ.…”
unclassified